Determination of the lymphocyte DNA resistance to oxidative damage imparted by the consumption of soy bean-supplemented diet in the Murine model using single cell gel electrophoresis assay - Lizaso, Analyn A.
The mammalian cell needs to maintain a delicate balance between the amount of free radicals and its anti-oxidant system for optimum performance. Oxidative stress results with there is an imbalance between these two components, with an increase in the relative amount of free radicals versus anti-oxidants. To counter oxidative stress, the balance should be shifted back by increasing the amount of anti-oxidants.Several compounds have been identified as potent anti-oxidants. One of these compounds is known collectively as isoflabonoids. Found primarily in soybeans, isflavonoids have been shown to possess anti-oxidant properties following in vitro and in vivo studies. Among the isoflavonoids, genistein is the most important agent that has been extensively investigated for its chemopreventive and anti-cancer activity (Wei et al., 2003).Oxidative damage can be best demonstrated by observing for effects on DNA resistance in affected cells using various laboratory methods. One such method, called single cell gel electrophoresis (SCGE) assay, had been shown to be the method of choice for evaluation low degrees of DNA damage in individual cells. The SCGE assay had been useful in the study of several important anti-oxidants, such as lycopene from tomatoes, resveratrol from grapes and soymilk. The SCGE assay was adapted for use in this study.The overall objective of this study was to determine whether genistein in soybeans can impart protection against DNA damage on lymphocytes using SCGE in the murine model.
Sixty-four BALB/c mice, (32 males and 32 females) about 6 to 8 weeks old, 18 to 22 grams in weight, were randomly divided into four diet / treatment groups. There were three treatment groups consisting of different dosages (50 mg, 250 mg and 500 mg) of genistein per kg diet. One group served as the negative control group. Corresponding intervention were administered ad libitum and was carried out of six weeks. Blood were collected and were used for the single cell gel electrophoresis (SCGE) assay for the evaluation of the DNA damage and for the time-resolved fluorescence immunoassay (TR-FIA) for the quantitation of the plasma genistein concentration.Based on the evaluation of DNA damage, for the treatment groups of both sexes, as the dose increases and the intervention proceeds, the mean relative tail moment and percentage of cell damage decreases. It can be noted that there is an inverse effect between the dose of the intervention and the mean outcome.In addition, plasma genistein concentration of pooled samples as well as the genistein concentration of the respective diets were determined using TR-FIA. There was a significant increase in the plasma genistein concentration as compared from the baseline and this increase was seen to be dose dependent. It was also inferred that there is a correlation between the plasma genistein concentration and level of DNA protection.It can be concluded from these results that lymphocytes of soybean-supplemented mice were shown to have an increased resistance to oxidative damage when challenged ex vivo with 600 uM of hydrogen peroxide in a dose and time dependent manner.However, death of several female members of the intervention group warrants further investigation. Investigation is recommended on the toxicity and estrogenic effect of soy supplementation with particular attention on the age of the animal subjects.
Thesis (MS Biochemistry)--University of the Philippines Manila
Keywords: DNA damage